Tartrate stabilisation of Rosé wine using ion exchange resins - Borges, Rita (2019)
Tartaric stabilisation is essential to satisfy the quality criteria of wines. To prevent wine tartaric precipitates, potassium hydrogen tartrate (KHT) and calcium tartrate (CaT), several techniques can be used. The addition of oenological products, such as metatartaric acid and carboxymetilcelulose (CMC’s) as well as the use of ion exchange resins are acceptable techniques for tartaric stabilization by the OIV, according to Resolution 43/2000. The aim of this study was to evaluate the ion exchange resins effect on wine tartaric stabilization efficiency and wine quality, compared to effect of the addition of different oenological additives. A Rosé wine from 2015 vintage, Douro region, was used for the experiments. Ion exchange resin versus CMC’s, with different structural features (Guise et al. 2014), and metatartaric acid were tested concerning wine tartaric stabilization, physicochemical and sensory characteristics. As expected, all treatments stabilized the Rosé wine. After treatment with ion exchange resins, Rosé wine pH was lower and consequently wine acidity increased. Also, mineral composition (magnesium, calcium, potassium and sodium) decreased after treatment with ion exchange resins. In general, in wines treated with ion exchange resins, there are a decrease in polymeric pigments and colour intensity. Sensory analyses of this wine also showed, for the visual descriptor, colour intensity and limpidity attributes, that they were lesser and higher scored, respectively. Results from this preliminary study suggest that ion exchange resins could be an effective alternative for wine tartaric stabilization.